2003
DOI: 10.1046/j.1528-1157.2003.128902.x
|View full text |Cite
|
Sign up to set email alerts
|

Talampanel, a New Antiepileptic Drug: Single‐ and Multiple‐dose Pharmacokinetics and Initial 1‐Week Experience in Patients with Chronic Intractable Epilepsy

Abstract: Summary:Purpose: Talampanel (LY300164), a potent and selective ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)-receptor antagonist, is a potential new antiepileptic drug (AED). This study examines the single-and multiple-dose pharmacokinetics, safety, and tolerability of talampanel in patients with intractable epilepsy and assesses the potential for pharmacokinetic interaction.Methods: Eleven of 14 patients entered into the study completed. Fourteen patients were evaluated for safety, 13 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…Dizziness and ataxia were the only significant adverse events; importantly, there were no reports of cognitive or psychomotor impairment. However, other studies have noted that talampanel causes drowsiness (66,67). Additional larger scale trials with talampanel have been completed but since development of the drug has been terminated, it can be concluded that these larger trials were not promising.…”
Section: Human Studies With Ampa Receptor Antagonists In the Treatmenmentioning
confidence: 97%
“…Dizziness and ataxia were the only significant adverse events; importantly, there were no reports of cognitive or psychomotor impairment. However, other studies have noted that talampanel causes drowsiness (66,67). Additional larger scale trials with talampanel have been completed but since development of the drug has been terminated, it can be concluded that these larger trials were not promising.…”
Section: Human Studies With Ampa Receptor Antagonists In the Treatmenmentioning
confidence: 97%
“…One 2,3-benzodiazepine, talampanel (GYKI 53773; LY300164), has shown efficacy in clinical trials. 262,263 Nonetheless, it is unclear whether AMPA receptor antagonists will be tolerable at therapeutic doses. In animal models, such agents generally cause neurological impairment at doses near those that confer seizure protection.…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%
“…Both GYKI 53405 and talampanel are protective in the MES test in mice and also in various chemoconvulsant models, but only at doses near those that cause motor side effects (Andrási, 2001). In clinical trials talampanel has been reported to be well tolerated, but sedation may occur, especially with initial dosing (Chappell et al, 2002;Langan et al, 2003;Danielsson et al, 2004).…”
Section: Ampa Receptor Antagonistsmentioning
confidence: 99%